THE EFFECT OF CLAY-MADE GRANULES MATERIAL ON THE VEGETABLES HYDROPONIC GROWTH WITH WICK SYSTEMS - Marlina, Iis; Triyono, Sugeng; Tusi, Ahmad (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2015)
This study aimed to determine the effect of granule growing media on growth and yield of vegetables in a hidroponic wick system. The design of this study used Randomized Complete Block (RCB) with factorial arrangement and three replications. The first factor consisted of three levels : kale (S1), spinach (S2), and mustard (S3). The second factorwere the size of the granules with four levels : 12mm (M1), 6mm (M2), 4 mm (M3) and husk char (M4) as a control. Each plant was grown in a wicked pot. There were 12 treatment combinations, with three replicates. Parameters observed were physical properties of the media, evapotranspiration, number of leaves, growth, biomass, and yield. Data was analyzed using the Analysis of Variance (ANOVA) 1%and 5%levels of significance, followed by LSDcomparision. Results showed that therewas no significant interaction betweenmedia and types of plant. However; sizes of media significantly affected the evapotranspiration, growth, biomass, and yield. Keywords:Wicked, hydroponics, granules, media, vegetables